High prevalence of anti-hepatitis A IgG in a cohort of UK HIV-negative men who have sex with men: implications for local hepatitis A vaccine policy. (September 2018) - Bhagey, A; Foster, K; Ralph, S; Wardropper, A; White, C; Wholey, V; Duncan, S
BASHH guidelines recommend that 'the hepatitis A virus total antibody test can be offered to at-risk patients whose immune status is unknown … depending on local funding arrangements'. We sought to measure the local prevalence of anti-hepatitis A (HAV) IgG in HIV-negative men who have sex with men (MSM), to inform the utility of pre-vaccination screening. We assessed the prevalence of anti-HAV IgG in HIV-negative MSM who attended sexual health services in County Durham and Darlington, UK, from March to August 2017. Data were extracted from electronic patient records and analysed in Excel. Our study was granted local Caldicott approval. Seventy four per cent of 244 HIV-negative MSM who attended for review were screened. Anti-HAV IgG was detected in 42% who did not report definite previous infection or vaccination; not detected in 57.4%; and was equivocal in 0.6%. Vaccine was administered to 48% of eligible patients. The estimated financial costs of universal vaccination of MSM (£4235.40) and pre-vaccination screening with vaccination of susceptible patients (£4188.13) are similar. Pre-vaccination screening and vaccination of susceptible patients does not save resources compared to a policy of universal vaccination of MSM in our setting. Universal vaccination of MSM attending genitourinary medicine clinics may improve vaccine uptake.